1995
DOI: 10.1136/jnnp.58.1.56
|View full text |Cite
|
Sign up to set email alerts
|

Amyotrophic cervical myelopathy in adolescence.

Abstract: The clinical and radiological features in seven patients who had asymmetric muscular atrophy of the hand and forearm when young are reported and a new hypothesis for its aetiology is proposed. Investigation of body growth curves (a surrogate for velocity of arm growth) showed close relation between (a) the age when the body height increased most rapidly and the onset age of this disorder, and (b) the age when the rapid body growth period ended and the age when symptom progression ceased. Cervical radiological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
52
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(52 citation statements)
references
References 13 publications
0
52
0
Order By: Relevance
“…Yada and colleagues have pointed out a rostral shift of the posterior root entry zone of the middle and lower cervical spinal cord on neck-flexed myelogram in nine cases of CFM. They hypothesized that the spinal cord could be stretched in an up-down direction due to growth imbalance between a long cervical spine and a short spinal cord (overstretch mechanism) [21,51,52]. Tachibana et al conducted an experimental study on a canine model of overstretching spinal cord [46,47].…”
Section: Pathophysiology Of Cfmmentioning
confidence: 99%
“…Yada and colleagues have pointed out a rostral shift of the posterior root entry zone of the middle and lower cervical spinal cord on neck-flexed myelogram in nine cases of CFM. They hypothesized that the spinal cord could be stretched in an up-down direction due to growth imbalance between a long cervical spine and a short spinal cord (overstretch mechanism) [21,51,52]. Tachibana et al conducted an experimental study on a canine model of overstretching spinal cord [46,47].…”
Section: Pathophysiology Of Cfmmentioning
confidence: 99%
“…We and others have reported dynamic changes of the cervical dural sac and spinal cord during neck flexion in case series of this illness. [9][10][11][12][13] We further investigated if those dynamic changes are characteristic of this illness and contribute to the pathogenesis.…”
mentioning
confidence: 99%
“…3,4 Moreover, clinical studies have also shown that profound desaturations below 90% were significantly correlated with hemispheric lateralization in localization-related epilepsy (odds ratio right vs left 5 2.098; 95% confidence interval 1.078-4.085). 5 The knowledge about lateralization of the anatomy and pathophysiology of the central autonomic nervous system may contribute to a better understanding of SUDEP and has the potential to detect patients who may be particularly susceptible to this devastating clinical entity. …”
Section: Autonomic Changes With Seizures Correlate With Postictal Eegmentioning
confidence: 99%